PENGEMBANGAN MENU DIET SEHAT BERBASIS AMPAS TAHU DAN TIWUL UNTUK MAHASISWA UNIVERSITAS AISYAH PRINGSEWU - Wati, Desti Ambar; Kusuma, Devi; Putri, Fadhilah Azzahra Wijaya; Amelia, Siska; Fitriani, Adina; Ulfatunnisa, Zahratul Aini; Salsabilla, Suci Aisyah (Poltekkes Kemenkes Riau, 2025)
Overweight among adolescents, including university students, continues to rise and poses long-term health risks. One preventive approach is through education and healthy food processing using local ingredients. This community service program aimed to improve students' knowledge and skills in preparing healthy steak made from tiwul (cassava granules) and tofu dregs. The activity was conducted in April–May 2025 and involved 15 students from Aisyah University of Pringsewu. The methods included nutrition education, product demonstration, and sensory evaluation. Results showed high enthusiasm from participants, who actively engaged in all stages of the activity. The developed product had acceptable taste and texture, and was high in dietary fiber, supporting weight management goals. This program proved that healthy, affordable food can be made from local resources and food by-products using simple techniques. Students are expected to apply this knowledge at home and serve as role models in promoting healthy eating habits among their peers.